2002
DOI: 10.1016/s0378-1097(02)00455-x
|View full text |Cite
|
Sign up to set email alerts
|

ITS region of Pythium canariense sp. nov., its morphology and its interaction with Botrytis cinerea

Abstract: A new species Pythium canariense (CI-07), isolated from soil samples taken in the San Nicolas region of the Canary islands (Gran Canaria, Spain), is being described here. This species is characterised by its spherical to pyriform, intercalary to catenulate sporangia, smooth-walled terminal oogonia supplied with monoclinous and diclinous antheridia which at times are branched and wrap around the female gametangia. The fungus has an antagonistic effect on Botrytis cinerea, the grey mould fungus. Morphological fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Antarctic isolates are globose and fall into the size ranges given for species in this group (van der Plaats-Niterink, 1981;Paul, 2002). The most striking morphological feature of the Antarctic isolates are the chlamydospores that were seen in the plant tissue and older PDA cultures, and there is some anecdotal evidence that these are frequently observed in field isolates from other Antarctic sites (K.K.…”
Section: Discussionmentioning
confidence: 99%
“…Antarctic isolates are globose and fall into the size ranges given for species in this group (van der Plaats-Niterink, 1981;Paul, 2002). The most striking morphological feature of the Antarctic isolates are the chlamydospores that were seen in the plant tissue and older PDA cultures, and there is some anecdotal evidence that these are frequently observed in field isolates from other Antarctic sites (K.K.…”
Section: Discussionmentioning
confidence: 99%
“…Together with the rapid development of molecular biology techniques, rDNA-ITS sequence analyses have been widely used in pathogen identification and systems development research, including studies on Colletotrichum, Puccinia and Phytophthora [12][13][14][15][16][17][18][19][20][21], which may provide new pathways for advanced research on Physalospora piricola in molecular biology field. In Henan province and Liaoning province, as the traditional major apple producing areas in north China, the apple production was seriously affected by apple ring rot disease.…”
Section: Introductionmentioning
confidence: 99%
“…The internal transcribed spacer (ITS) region of the rRNA gene sequences has become a useful tool in Pythium taxonomy and can be used for identifying or detecting different Pythium spp. (Paul, 2002a, b; Levesque & de Cock, 2004). Variability seems appropriate for studies at the species level as demonstrated by numerous works (Allain‐Boule, 2004).…”
Section: Introductionmentioning
confidence: 99%